Benefits of pulmonary rehabilitation in patients with advanced lymphangioleiomyomatosis (LAM) compared with COPD – a retrospective analysis - Gloeckl, Rainer (Orphanet J Rare Dis, 2020)
ABSTRACT: Lymphangioleiomyomatosis (LAM) is a rare and progressive cystic lung disease with limited therapeutic options. We retrospectively analyzed the effects of a comprehensive 4-week inpatient pulmonary rehabilitation (PR) program in 58 patients with advanced LAM (FEV1: 45 ± 34%predicted, 6-min walk distance (6MWD): 338 ± 167 m). Exercise performance (6MWD: + 49 ± 50 m; p < 0.001) and quality of life (SF-36 physical component: + 2.4 ± 7.8 points; p = 0.049 and mental component: + 5.2 ± 12.1 points; p < 0.001) increased significantly after PR comparable to an COPD cohort. There were no clinical parameters that predicted changes in outcomes following PR. PR seems to be an effective therapeutic option even in patients with advanced LAM. TRIAL REGISTRATION: Clinical-Trials registration number: NCT04184193; date of registration: December 3, 2019.